Desenvolvimento e aplicação de método por UHPLC-MS/MS para determinação de fármacos em efluentes tratados em sistemas de wetlands construídos - Schwaickhardt, Rômulo de Oliveira (2021)
The growth in production and consequently in the use of pharmaceuticals and personal care products over the years has made domestic effluents generated both in large cities and in small cities loaded with these compounds, making it practically impossible to find urban effluents free of these residues. This exponential increase was not followed by conventional effluent treatment plants. Thus, new treatment alternatives such as constructed wetlands emerge as a potential technology for removing these contaminants from effluents. Therefore, to evaluate the efficiency of this and other types of effluent treatment systems, it is necessary to develop multiclass methods to control the treatment. In this work, a multiclass method was developed for the analysis of 37 compounds among drugs in raw and treated effluent from wetlands constructed in different configurations. The determination was performed by ultra performance liquid chromatography coupled to mass spectrometry (UHPLC-MS/MS). The solid phase extraction method (SPE) was developed using Oasis HLB cartridge, the sample percolated at pH 5 and with 0.01 mol L-1 of EDTA was eluted with methanol and a subsequent step of cleaning the extract with PSA sorbent was added. (d-SPE). The method showed recoveries between 70 and 120%, precision and intermediate precision (RSD ≤ 20%). The limit of quantification (LQ) was between 0.025 and 0.100 μg L-1 and the detection limit between 0.008 and 0.030 μg L-1. The validated method was applied to evaluate the removal of drugs present in the effluent after passing through a system of wetlands built with 4 different treatment configurations. The 14 compounds found in the raw effluent, only 8 were still detected and in lower concentrations after the constructed wetlands system in best configuration.